Strategi Da’i Dewan Dakwah Islamiah Indonesia Dalam Memperkuat Akidah dan Meningkatkan Ekonomi Umat - Syahrizal; Muhamad Zen; Fatmawati (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to examine the strategic role of the Dewan Dakwah Islamiah Indonesia (DDII) in strengthening the Islamic faith (aqidah) and improving the economic welfare of the Muslim community through its various da'wah programs. DDII is one of the Islamic missionary organizations that consistently provides religious guidance, especially in remote and underdeveloped areas where access to religious education and economic empowerment is still limited. This research employs a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. The data were analyzed using techniques of data reduction, data presentation, and drawing conclusions systematically. The results of the study show that DDII implements several strategies to spread Islamic teachings that focus on reinforcing the community’s faith, particularly targeting individuals who are not yet reached by da'wah efforts or who live in areas with limited access to religious education. These strategies include deploying da’i (preachers) to rural and isolated regions, conducting regular religious guidance, and providing accessible educational materials for laypeople. In addition, DDII actively promotes economic empowerment through community-based programs such as entrepreneurship training, the development of Islamic cooperatives, and the strengthening of household economies. By integrating spiritual da'wah and economic development, DDII seeks to create a society that is not only strong in its religious beliefs but also economically self-reliant. This research highlights the crucial role of Islamic missionary organizations in balancing religious guidance and socio-economic welfare in Muslim communities, fostering holistic community development in line with Islamic values.